The Expected Economic Impacts of Sudan's Accession to the WTO: The Case of the Banking Sector 1970-2008 - Elhag, Abubakr Eltigani (Arab Journal for Sciences and Research Publishing, 2025)
This study investigated the anticipated economic impacts of Sudan’s accession to the World Trade Organization (WTO), focusing on the banking sector’s role from 1970 to 2008, prior to South Sudan’s secession. The research aims to support Sudan’s preparation for WTO membership by analyzing the effects of financial liberalization, which has yielded both positive and negative outcomes in other developing countries. Employing a dual methodology combining empirical and descriptive approaches, the study relies on secondary data sources. It hypothesizes that Sudanese financial indicators positively correlate with growth indicators and that financial reforms contribute to financial development and economic growth. Results, derived in two stages, indicate that financial indicators significantly explain only two of four growth indicators, attributed to inadequate financing of the agricultural sector. The second stage confirms the partial presence of prerequisites, such as sound institutions and macroeconomic stability, necessary for effective financial liberalization. The study anticipates that WTO accession will enhance domestic bank efficiency and supervision. Recommendations include addressing barriers to financing the agricultural sector, strengthening central bank measures to tackle non-performing loans, and raising awareness among monetary authorities of the significant negative relationships between certain growth and financial indicators.
Keywords: Economic impacts; financial indicators; Sudan’s WTO accession; banking sector; financial liberalization; economic growth